Dipyridamole combined with exercise for thallium-201 myocardial imaging. - Walker, P R (1986)
A new stress test for thallium-201 myocardial imaging in which pharmacological coronary vasodilatation with dipyridamole is combined with dynamic exercise is described. In 38 patients with coronary artery disease the sensitivity, total number of defects, degree of redistribution, and visual quality of thallium-201 imaging were greater after dipyridamole with exercise testing than after exercise alone. When the data from these 38 patients were combined with the results of dipyridamole-exercise imaging in 49 patients in whom exercise electrocardiography had been inconclusive then the technique gave a sensitivity for coronary disease of 87% and a specificity of 92%. Dipyridamole also increased the sensitivity of the exercise electrocardiogram, so that no patient with coronary disease had a strictly negative dipyridamole-exercise stress test. Only five of 214 patients who have now undergone this test have had complications requiring reversal of vasodilatation with aminophylline. The combined use of dipyridamole and exercise in this simple technique is a reliable and safe improvement on standard thallium-201 imaging tests.